Bank's influence and firm's performance / Nofirda Muhamad - Muhammad, Norfirda (2007)
Objective: This study involved three objectives. First, this study aim to investigate whether there is any significant effect of bank influence on the performance of firms. Second, this study plans to identify whether there is any significant effect of other factors n the performance of firm beside bank influence. Lastly this study, intend to identify nether there is any significant difference between performance of dependent and independent firms. Methods: This study used Single Linear Regression to achieve the first objective. Meanwhile, Multiple Linear Regression model was used to identify whether there is any significant effect of other factors on the performance of firm beside bank influence, while dependent Group t-test model was used in order to identify whether there is any significant difference of performance between dependent and independent firms. The variables involved in this study are total fixed asset, net income, market to book value ratio, shareholders' equity and total debt. Findings: This study found that, there is a significant effect of bank's influence on performance of firm. Moreover, this study also revealed, there is a significant effect of - bank shareholder' equity on the performance of firm. In addition the results also show the positive relationship between shareholders' equity and performance of firm. On the other hand, this study proved, there are no significant effects of both net income and market to book value ratio on the performance of firm. Other than that, this study suggested, there is significant difference between dependent and independent firms' performance. Whereby, mean difference equal to 237015.05.